Comparison of Mobile Web Browsers for Smartphones. Issue 1 (2nd January 2018) - Ahn, Junyoung; Kim, Kyungdoh; Proctor, Robert W.
ABSTRACT: Previous studies on mobile Web browsers have focused on phone features and technical performance, but not on the user interface. In this study, we compared three mobile Web browsers in the iPhone and ultimately proposed recommendations for the design of mobile Web browsers for smartphones. To develop such recommendations, we redefined the user interface (UI) components of mobile Web browsers from previous studies to conform to smartphones and compared the Chrome, Safari, and Opera Mini-browsers. To do this, we conducted experiments on usability tests with several dependent variables, including usefulness, perceived time reduction, minimal action, usability, ease to memorize, learnability, fun, and satisfaction. Finally, we developed several recommendations, based on the experimental results and participant interviews, which will fulfill user needs for the interface design of mobile Web browsers for smartphones. Multi-windows need to be implemented in a 3D environment. Developers should consider UI components and features that ease learning how to use the browser for novice users.